Performance of Gallus gallus domesticus Induced by Turmeric (Curcuma longa L.) Powder before Puberty - Sukarman Hadi Jaya Putra; Yohanes Bare; Mansur S; Oktavius Yoseph Tuta Mago; Yohanes Nong Bunga; Yohanes Boli Tematan (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2022)
The lack of use of turmeric powder by farmers to increase the production of native chicken eggs such as increasing egg weight. The purpose of the research was to determine the effect of turmeric powder supplement (Curcuma longa L.) on the weight of native chicken eggs (Gallus gallus domesticus) that had been induced on standard feed before entering the pebertas period. The design of this study is to use a complete randomized design with a total of 3 treatments. Treatment consists of the first; chicken that is not given turmeric powder supplement (P0). Second; native chickens are given turmeric powder supplements at a dose of 216 mg/ chicken /day (P1). Third; is a native chicken given turmeric powder supplement with a dose of 324 mg/ chicken /day. Egg weight data is obtained from the results of measurements made every day when all chickens have laid eggs. One month's measurement data is taken from 28 days of measurement. All measurement data is analyzed with analysis of variance (ANOVA). If the data is influential, it is then tested with a Duncan test with a trust of 95 % (α>0.05). Supplementation of turmeric powder mixed in daily standard feed before entering puberty can have an effect on increasing the weight of free-range chicken eggs (Gallus gallus domesticus). There was a significant difference in free-range chickens that were given turmeric powder supplements at a dose of 324 mg/ chicken /day (483.6 mg) compared to chickens that did not receive turmeric powder supplements (405.4 mg).